Relationship Between Service Quality of the Marine Leisure Sports, and Behavioral Intention of the Participants - Chun-Ho Yang, Kyung-Seok Han (International Journal of Advanced Science and Technology, 2020)
Background/Objectives: The purpose of this study was to identify the relationship between service quality of marine leisure sports and behavioral intention. The subjects were asked to complete the questionnaire using the self-administration method.